Thermostability of seven hepatitis C virus genotypes in vitro and in vivo. Issue 7 (17th January 2013) - Doerrbecker, J.; Meuleman, P.; Kang, J.; Riebesehl, N.; Wilhelm, C.; Friesland, M.; Pfaender, S.; Steinmann, J.; Pietschmann, T.; Steinmann, E.
Summary Hepatitis C virus (HCV) is transmitted primarily through percutaneous exposure to contaminated blood especially in healthcare settings and among people who inject drugs. The environmental stability of HCV has been extrapolated from studies with the bovine viral diarrhoea virus or was so far only addressed with HCV genotype 2a viruses. The aim of this study was to compare the environmental and thermostability of all so far known seven HCV genotypes in vitro and in vivo. Incubation experiments at room temperature revealed that all HCV genotypes showed similar environmental stabilities in suspension with viral infectivity detectable for up to 28 days. The risk of HCV infection may not accurately be reflected by determination of HCV RNA levels. However, viral stability and transmission risks assessed from in vitro experiments correlated with viral infectivity in transgenic mice containing human liver xenografts. A reduced viral stability for up to 2 days was observed at 37 °C with comparable decays for all HCV genotypes confirmed by thermodynamic analysis. These results demonstrate that different HCV genotypes possess comparable stability in the environment and that noninfectious particles after incubation in vitro do not cause infection in an HCV in vivo model. These findings are important for estimation of HCV cross‐transmission in the environment and indicate that different HCV genotypes do not display an altered stability or resistance at certain temperatures.